0649 Are Self-Reported Symptoms of Obstructive Sleep Apnea Associated with Increased Nightmare Frequency?. (12th April 2019) - Brown, Aurora; Tompkins, Brooke; Messman, Brett; Wardle, Sophie; Slavish, Danica C; Kelly, Kimberly; Ruggero, Camilo; Taylor, Daniel J
Abstract: Introduction: Nightmares involve disturbing images and create distress in many individuals. Approximately 50-80% of the general population reports experiencing regular nightmares or stress dreams. Previous research suggests that lapses in breathing during sleep may induce nightmares. Therefore, the present study examined if obstructive sleep apnea symptoms were associated with greater nightmare frequency in nurses. Methods: Participants were 461 nurses (91.1% female; 77.7% white, mean age = 39.03 ± 11.07) recruited from two hospitals as part of a larger parent study, "Sleep and Vaccine Response in Nurses (SAV-RN)." Participants completed self-report measures to screen for obstructive sleep apnea (OSA; via the STOP) and for frequency of nightmares per week. Linear regression was used to assess the association between STOP total score and nightmare frequency. An exploratory linear regression was then used to further assess the associations between each OSA symptom (snoring, daytime fatigue, observed airway obstruction at night, and high blood pressure) and nightmare frequency. Results: Of the sample, 236 nurses (51.3%) reported having nightmares at least one night a week. Greater OSA symptoms were associated with reporting a greater frequency nightmares per week (β = 0.15, SE = 0.04 p <.001). Endorsement of daytime fatigue was associated with reporting a greater frequency nightmares per week (β = 0.36, SE = 0.07 p = <.001); however, the endorsement of the other individual symptoms that make up the criteria for OSA were not associated with nightmare frequency. Conclusion: Our research suggests that greater overall OSA symptoms and the specific daytime fatigue symptom may be associated with greater nightmare frequency, but snoring, observed airway obstruction, or high blood pressure were not associated with increased nightmare frequency in nurses. Assessing and targeting the comorbid OSA symptoms in nightmare disorder may be important for the effective treatment of nightmares and may help reduce daytime fatigue. Future studies should seek to replicate these associations using polysomnography diagnostic criteria for OSA. Support (If Any): NIAID R01AI128359-01 (PIs: Taylor & Kelly)